Jala: Jibana Pain - Jayakrushna Panigrahi; Sundra Narayan Patra (Bhubaneswar: Odisha Pariparshwika Samiti, 2004)
The book is related to environmental Science
Keywords: Odia; Jala: Jibana Pain; Enivronmental Science; Odia; Odia